Comparative studies of Trypanosoma (Duttonella) vivax isolates from Colombia - Dirie, M.F.; Otte, M.J.; Thathi, R.; Gardiner, Peter R. (Cambridge University Press, 1993)
The characterization of fourTrypanosoma vivaxisolates from Colombia in South America showed that although minor phenotypic differences existed between them, these parasites are antigenically related and belong to a single serodeme. Characterization by isoenzyme assay, karyotyping and DNA probe analysis, showed the Colombian isolates to be more similar to the West African than to KenyanT. vivax. There was, however, little serological cross-reactivity between South American and African groups ofT. vivax. Although theT. vivaxisolates from Colombia were pathogenic for dairy calves which showed the typical sign of progressive emaciation, these parasites failed to infect mice or tsetseand could not be cultivated as bloodstream formsin vitro.This study represents initial attempts to establish the phenotypic and serological diversity amongstT. vivaxisolates from South America.